2010
DOI: 10.1080/00071661003746503
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrient density and lighting regime in broiler chickens: Effect on antioxidant status and immune functiona

Abstract: 1. The effects of nutrient density and lighting regime on oxidant status and immune function of broilers were investigated in a 2 x 4 experimental design (8 groups of 576 chickens). 2. There were two nutrient densities: high (H) starter diet AME 13.39 MJ/kg, 230 g crude protein (CP)/kg: finisher 13.39 MJ/kg, 197 g CP/kg CP) and low (L) starter AME 12.03 MJ/kg, 208 g CP/k; finisher 12.14 MJ/kg, 183 g CP/kg C. The 4 lighting regimes were continuous (CL) 23L:1D, 20L:4D (12L:2D:8L:2D), 16L:8D (12L:3D:2L:3D:2L:2D) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…The finding of longer photoperiod being pro-oxidative to broiler muscles has been corroborated by Li et al [17] who observed a higher MDA in the fillet muscles from 23L:1D compared to 12L:12D. In addition, Guob et al [18] reported that a 12L:12D treatment decreased the serum MDA content compared to 20L:4D. The findings were further supported by a reported trend of greater activity of superoxide dismutase, a well-known indicator of antioxidative capacity, in 16L:8D and 12L:12D treatments compared to 23L:1D and 20L:4D treatments [18].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The finding of longer photoperiod being pro-oxidative to broiler muscles has been corroborated by Li et al [17] who observed a higher MDA in the fillet muscles from 23L:1D compared to 12L:12D. In addition, Guob et al [18] reported that a 12L:12D treatment decreased the serum MDA content compared to 20L:4D. The findings were further supported by a reported trend of greater activity of superoxide dismutase, a well-known indicator of antioxidative capacity, in 16L:8D and 12L:12D treatments compared to 23L:1D and 20L:4D treatments [18].…”
Section: Discussionmentioning
confidence: 67%
“…Previously, Li et al [17] found that breast meat from broilers reared under a 12L:12D photoperiod has lower malondialdehyde (MDA, a secondary lipid oxidation product) concentrations compared to 23L:1D controls. Guob et al [18] corroborated this finding, reporting higher blood serum MDA levels in broilers reared at a longer photoperiod, indicative of increased oxidative stress. It has been well-established that chronic stress is detrimental to broiler meat quality and oxidative stability [19][20][21].…”
Section: Introductionmentioning
confidence: 75%
“…Further, the results were in accord with Duve et al (2011) who reported that splitting a long dark period into two shorter periods separated in time might reduce the negative implications of an extended dark period. As well, the 12L:12D IL schedule in particular might enhance immune function in broilers (Guo et al, 2010). It was apparent from the current study that dark does have an important impact on the health parameters measured, which could in turn alter broiler welfare and immune performance.…”
Section: Serum Biochemical Parametersmentioning
confidence: 86%
“…Olanrewaju et al [27] reported that commercial broiler generally exposed to 24h to 23h lighting in the fattening period. It was observed that the lipid oxidation decreased in broiler exposed to 12h light regime compared to broiler exposed to 23h, 20h and 16h light regime [22]. In addition, stocking density is a crucial factor for broiler as high stocking density can cause stress in broiler as a consequence lowers performance and higher mortality observed in broiler [23].…”
Section: L-arginine and Stressmentioning
confidence: 99%
“…Definitely chicken are always suffers from different kind of stress during rearing time including photoperiod time [22], stocking density [23], noise level (Campo et al 2005) [24], cold stress [25] and during marketing transport stress one of the major stress in broiler [26]. It is well known fact that different kind of stress associated with oxidative damage in poultry.…”
Section: L-arginine and Stressmentioning
confidence: 99%